Greenhouse Gas Emissions From Cropping and Grazed Pastures Are Similar: A Simulation Analysis in Australia - Meier, Elizabeth A.; Thorburn, Peter J.; Bell, Lindsay W.; Harrison, Matthew T.; Biggs, Jody S. (Frontiers in Sustainable Food Systems, 2020)
The agricultural sector has potential to provide greenhouse gas (GHG) mitigation by sequestering soil organic carbon (SOC). Replacing cropland with permanent pasture is one practice promoted for its potential to sequester soil carbon. However, pastures frequently support livestock, which produce other GHG emissions that could negate the abatement from increased SOC, especially given the declining rate of SOC sequestration through time. Our purpose was to determine whether the abatement provided by SOC storage in permanent pastures was offset by livestock emissions, and to thus compare emissions from grazed pasture systems with those from cropping systems. We investigated this question for three case study farms in locations with contrasting climate, soils and management representative of Australian cropping and livestock systems. Three cropping scenarios were defined that had increasing amounts of SOC inputs: Cropburn, crop residues burned before sowing (lowest SOC input); Cropstubble, crop residues retained; and Cropintensity, uncropped fallow phases replaced with short-term green manure legume crops. The on-farm GHG emissions profiles of these cropping scenarios were compared with those from two livestock scenarios utilizing continuous stocking: Livestockgrass, stocked permanent grass pasture; and Livestocklegume, stocked permanent legume pasture; the latter having higher SOC input than the former. Crop yields, pasture growth rates and emissions of carbon dioxide (CO2) and nitrous oxide (N2O) from the soil were simulated with the APSIM farming systems model. Livestock emissions were predicted using Australian GHG accounting emission factors. For the farms in this study, the SOC sequestered in the stocked permanent pastures was offset by emissions from livestock, and emissions from cropping scenarios were similar to or significantly less than those from the livestock scenarios. These findings: (1) demonstrate the importance of using net GHG abatement potentials from combined emissions rather than a single GHG abatement process when evaluating potential abatement practices, and (2) question the potential for GHG mitigation through the agricultural sector because climate and soil characteristics in different locations can alter the abatement potential of management practices, and because change in management practice can have feedbacks on other management practices and hence on GHG abatement potential.